Inside Cover: Ultramicropore Engineering by Dehydration to Enable Molecular Sieving of H2 by Calcium Trimesate (Angew. Chem. Int. Ed. 37/2020). Issue 37 (10th August 2020) - Mukherjee, Soumya; Chen, Shoushun; Bezrukov, Andrey A.; Mostrom, Matthew; Terskikh, Victor V.; Franz, Douglas; Wang, Shi‐Qiang; Kumar, Amrit; Chen, Mansheng; Space, Brian; Huang, Yining; Zaworotko, Michael J.
Abstract : Physical separations can be superior to chemical separations when it comes to energetics and kinetics, especially when ideal sieving is feasible among hard‐to‐separate gas mixtures. Unfortunately, for industrial gases a very precise pore window size, which must be ultramicroporous, is needed for ideal sieving. In their Research Article on page 16188, Y. Huang, M. J. Zaworotko, and co‐workers describe a new variant of Ca‐trimesate that offers just the right pore size (0.31 nm) to enable ideal sieving of H2 from CO2, two of the primary components of syngas.